Pharmacokinetics of inhaled styrene in rats and humans. - Ramsey, John C; Young, John D (Scandinavian Journal of Work, Environment & Health, 1978)
The pharmacokinetic profile of inhaled styrene was examined in rats exposed to levels of 80, 200, 600 or 1,200 ppm for periods of up to 24 h. At levels up to 200 ppm for 6 h, styrene was cleared from the blood according to a two-compartment linear pharmacokinetic model, but at levels of 600 ppm and above the clearance was saturated. In going from 80 to 1,200 ppm (a 15-fold increase), the area under the blood concentration/time curves (AUC) increased by a factor or 112. Fat tissue was shown to comprise the second compartment of the two-compartment pharmacokinetic model. It is suggested that saturation of styrene clearance is due mostly to saturation of the metabolic capacity for styrene. In humans exposed to 80 ppm of styrene for 6 h, styrene was cleared from the blood according to a two-compartment linear pharmacokinetic model similar to that for rats. A maximum blood concentration of 0.9 microgram/ml was reached at the end of the exposure. Most of the inhaled styrene was excreted in the urine as phenylglyoxylic and mandelic acids, and only a small amount as styrene in the expired air. Simulation of the pharmacokinetic model showed that no continued accumulation of styrene would occur during repeated, daily 8-h exposures to 80 ppm. These data reveal that the rat is a reasonable pharmacokinetic model for styrene in humans. At levels of exposure up to 200 ppm, styrene is cleared from the body very efficiently and will not continue to accumulate upon repeated exposure. But at levels of styrene sufficiently high to saturate the metabolic clearance capacity, the integrated dose (measured by the AUC) will be much greater than expected based on exposure levels alone. Therefore, the extrapolation of toxicity observed at high levels of styrene exposure to that expected at low levels may not be justified.
Keywords: human; inhaled styrene; mandelic acid; metabolism; pharmacokinetics; phenylglyoxylic acid; rat; styrene